2010
DOI: 10.3892/mmr_00000289
|View full text |Cite
|
Sign up to set email alerts
|

Association of endothelial nitric oxide synthase polymorphisms and haplotypes with ischemic stroke in Korean individuals with or without diabetes mellitus

Abstract: Abstract. Polymorphisms of the endothelial nitric oxide synthase (enoS) gene have been implicated in various diseases associated with cardiovascular risk factors, but little is known regarding the risks of ischemic stroke (iS) in patients with diabetes mellitus (dM). in this study, we evaluated the genotypes and haplotypes of three enoS polymorphisms (-786T>c, 4a4b and 894G>T) in a Korean population of 223 IS patients and 206 controls classified into four groups: healthy subjects, type 2 dM patients without iS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 15 publications
1
6
0
Order By: Relevance
“…[34][35][36][37] Lower nitric oxide plasma level was detected among 4a allele carriers than in the 4b wild-type allele. 31 A similar trend found in genotype-phenotype studies on NOS protein concentration and enzyme activity, indicates that protein expression and enzyme activity were lower in 4a4b genotype as compared to 4b4b genotype. 38 Moreover, the mutant 4a allele of eNOS may predispose a harmful effect on atherosclerosis, which is an independent risk factor for ischemic stroke.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…[34][35][36][37] Lower nitric oxide plasma level was detected among 4a allele carriers than in the 4b wild-type allele. 31 A similar trend found in genotype-phenotype studies on NOS protein concentration and enzyme activity, indicates that protein expression and enzyme activity were lower in 4a4b genotype as compared to 4b4b genotype. 38 Moreover, the mutant 4a allele of eNOS may predispose a harmful effect on atherosclerosis, which is an independent risk factor for ischemic stroke.…”
Section: Discussionsupporting
confidence: 62%
“…These findings are in agreement with several case-control studies. [10][11][12]31,32 Akhter et al 33 reported that lower levels of nitric oxide is associated with ischemic stroke, indicating that eNOS has a neuroprotective effect and play the role of endothelial dysfunction in ischemic stroke pathogenesis. Recently, meta-analyses have reported the significant association between eNOS 4a/b polymorphism and increased risk of ischemic stroke, particularly in Asian population rather than Caucasian population.…”
Section: Discussionmentioning
confidence: 97%
“…For this reason, in T-786C polymorphism, two articles [29], [30] for recessive model were not sufficient to calculated pooled OR. After excluding articles for OR>3.0 [32], [41], [42], there were only two studies left sufficient to calculated pooled OR for recessive model, so we did not further investigate the association in recessive model.…”
Section: Resultsmentioning
confidence: 99%
“…Data from 33 articles on the association between any of the three polymorphisms and ischemic stroke met the inclusion and exclusion criteria, and they were included in the meta‐analysis. There are 13 articles written in Chinese and 20 articles written in English. The final sample size was as follows: 5261 cases and 5823 controls for the G894T polymorphism, 4295 cases and 4682 controls for the 4b/a polymorphism, and 2698 cases and 3254 controls for the T786C polymorphism.…”
Section: Resultsmentioning
confidence: 99%
“…Data were extracted separately for these two ethnicities. Thus, 34 data sets were obtained: 25 data sets (24 articles) dealt with G894T , 18 with 4b/a , and 11 with T786C . One article that investigated 4b/a, and three articles that investigated T786C also investigated G894T.…”
Section: Resultsmentioning
confidence: 99%